Capital tax competition and household mobility - Wolfgang Eggert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
Capital tax competition is analyzed in a model with a single private and a locally supplied public consumption good. As a benchmark case necessary conditions for efficient interregional tax structures are derived and contrasted with the outcome of beggar thy neighbor strategies. If households are immobile an intervention of a central government can be justified to raise efficiency of the NASH equilibrium. In contrast, NASH equilibria are efficient if households are imperfectly mobile because regions have incentives to ensure an efficient interregional resource allocation via granting interregional transfer payments.
Keywords: 330; Kapitalertragsteuer; Steuerwettbewerb; Lokale öffentliche Güter; Binnenwanderung; Spieltheorie; Theorie